Analysis of the ergonomics of interfaces of popular e-marketing tools - Weronika Studzińska (Journal of Computer Sciences Institute)
This article analyses the ergonomics of the interfaces of selected e-marketing tools. The main aim of the study was to verify whether all the examined tools have a similar user interface quality. The research was conducted using the cogni-tive walkthrough method, a modified LUT list with WUP scores, and a questionnaire for assessing tool usability based on Nielsen heuristics. Three tools designed for Internet monitoring were analysed - Brand24, Mention and Awario. The experiment showed that, in terms of the ergonomics of the solutions, not all tools have a similar interface quality. For two of the analysed tools, similar results and ratings were obtained, while one of them presented a noticeably lower level.